PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK TANI JERUK KALAMANSI - Hermelin Saras Putri; Ririn Gusti (UNIB Press, Universitas Bengkulu, 2021)
This study aims to systematically obtain information related to community empowerment through kalamansi citrus farmer groups. The method used is the focus group discussion by getting the results that community empowerment through the kalamansi citrus farmer group was established in 2008, has 27 members, the natural lemongrass farmer group gets certificate of appreciation from the Governor of Bengkulu as an Independent Kalamansi Citrus Farm Farmer / Success in the Context of the 50th Anniversary of Bengkulu Province, on 18 November 2018. As time goes by, Kalamansi oranges have produced many fruits, the empowerment of sustainable natural lemongrass farmer groups in Padang lemongrass village is one of a form of community empowerment. The community usually sells it in the form of fresh fruit to market traders in the city of Bengkulu. With the empowerment of this sustainable natural fresh farmer group, the community can use their land as a kalamansi orange plantation where the products they plant will be traded in the market or to Mr. Amti who needing the raw material for kalamansi syrup, the community can increase their family's economic income by planting kalamansi and oranges the community also conserves kalamsi citrus fruit in the city of Bengkulu. Keywords: Empowerment, farmer groups, kalamansi oranges.